2008
DOI: 10.1111/j.1095-8649.2008.01947.x
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic telemetry to assess post‐stocking dispersal and mortality of razorback sucker Xyrauchen texanus

Abstract: Acoustic telemetry and scuba revealed immediate and high post-stocking mortality of razorback sucker Xyrauchen texanus in Lake Mohave, U.S.A., a Colorado River impoundment. At the conclusion of this 6 month study, only three of 19 (16%) study fish remained active. Concurrently, 20 X. texanus implanted with acoustic transmitters and held in a hatchery raceway remained healthy throughout the experiment and no transmitters were shed. Poststocking mortality was probably due to predation by striped bass Morone saxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…In the interim acoustic telemetry studies were performed with small numbers of razorback sucker at the potentially optimal stocking size of 500 mm TL and at the previously common release size of 380 mm TL to test the hypothesis. The results from these studies were unequivocal and confirmed the size-survival relationship, but survival also varied dramatically from year to year [22]. In addition, an acoustic tag that was implanted in a 520-mm TL razorback sucker was recovered from the stomach of a relatively average sized 13-kg striped bass by a fisherman [23], providing evidence that no size was completely safe from predation; the maximum length of razorback sucker is thought to be near a meter [24], but few individuals longer than 700 mm now are encountered [18,20].…”
Section: Research Adaptation and Emerging Technologysupporting
confidence: 62%
“…In the interim acoustic telemetry studies were performed with small numbers of razorback sucker at the potentially optimal stocking size of 500 mm TL and at the previously common release size of 380 mm TL to test the hypothesis. The results from these studies were unequivocal and confirmed the size-survival relationship, but survival also varied dramatically from year to year [22]. In addition, an acoustic tag that was implanted in a 520-mm TL razorback sucker was recovered from the stomach of a relatively average sized 13-kg striped bass by a fisherman [23], providing evidence that no size was completely safe from predation; the maximum length of razorback sucker is thought to be near a meter [24], but few individuals longer than 700 mm now are encountered [18,20].…”
Section: Research Adaptation and Emerging Technologysupporting
confidence: 62%
“…Females can be extremely fecund, with some of the larger individuals capable of producing more than 100,000 ova per year. Telemetry studies have shown that they are capable of considerable movement, including trips to multiple spawning areas within a season (Tyus and Karp 1990;Mueller et al 2000;Karam et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, knowledge of critical habitats and the movements among them is important for the protection of threatened species (Simpson & Mapleston, ; Ebner & Thiem, ). Movement and dispersal data can be used to refine stocking practices (Karam et al , ) and control programmes for invasive fishes (DeGrandchamp et al , ).…”
mentioning
confidence: 99%